OC-063 Pharyngeal Electrical Stimulation (pes) In Dysphagia Post-acute Stroke: A Double-blind, Randomised Trial. (9th June 2014) - Vasant, DH; Michou, E; Tyrrell, P; Jayasekeran, V; Mistry, S; O'Leary, N; Vail, A; Anwar, S; Gamble, E; Hamdy, S
Abstract : Introduction: Pharyngeal Electrical Stimulation (PES) is known to activate pharyngeal motor pathways. It has shown promise in acute stroke pilot studies, having improved swallowing function at 2-weeks. 1, 2 Methods: We aimed to recruit 100 hospitalised patients with new-onset dysphagia within 6 weeks of stroke at three Greater Manchester centres. Participants were randomised to either Active or Sham PES. Both interventions were delivered via an intraluminal pharyngeal catheter, left in situ for 10 min, once-daily for 3 days. Active intervention was delivered at optimal parameters (5Hz, at 75% maximum-tolerated intensity). The primary outcome measure was intended to be penetration-aspiration scores on videofluoroscopic assessment at 2-weeks. Owing to logistic difficulties with videofluoroscopy, prior to unblinding and analysis of data, we upgraded the dichotomised Dysphagia Severity Rating (DSR) scale, 2 assessed by independent, blinded speech therapists, to be the primary outcome: mild/no dysphagia (scores 0–3) or moderate-severe dysphagia (scores 4–12). We analysed under the intention to treat principle using logistic regression with an odds ratio (OR)/ Hazards ratio (HR) >1 indicating a favourable outcome for the active group. Results: We recruited 36 participants: median age 71y; 61% male, 92% moderate-severe dysphagia; 58% with enteral feeding tubes in-situ. At 2-weeks, 11/18 (61%) in the active group had DSR <4 compared with 9/18 (50%) in the sham group: OR (95% CI) = 2.53 (0.52 to 14.56). Patients in the active group also had shorter times to hospital discharge (39 vs. 52 days, HR (95% CI) of 1.19 (0.55, 2.57)) and removal of nasogastric feeding tubes (8 vs.14 days, HR (95% CI) of 2.01 (0.51, 7.93)). By 3 months, all but 3 patients in each group had DSR <4: OR (95% CI) = 1.0 (0.13 to 7.02). Conclusion: The observed differences are consistent with the hypothesised effect of PES in accelerating recovery of swallowing over the first 2-weeks following treatment. Lower than desired recruitment prevents definitive answers from this study but study design experience and outcome data reported here are essential to inform a definitive, multi-centre randomised trial. References: 1 Fraser, et al . 2002 2 Jayasekeran, et al . 2010 Disclosure of Interest: None Declared.